Fire-diffuse-fire model of dynamics of intracellular calcium waves - Dawson, S.P. (1999)
When Ca2+ is released from internal stores in living cells, the resulting wave of increased concentration can travel without deformation (continuous propagation) or with burst-like behavior (saltatory propagation). We analyze the 'fire-diffuse-fire' model in order to illuminate the differences between these two modes of propagation. We show that the Ca2+ release wave in immature Xenopus oocytes and cardiac myocytes is saltatory, whereas the fertilization wave in the mature oocyte is continuous.